Profiling cytokines in peritoneal effluent through a targeted multiplex cytokine panel provides novel insight into the localized proinflammatory processes in patients undergoing peritoneal dialysis - Okulewicz, Patrycja; Wojciuk, Bartosz; Wojciechowska-Koszko, Iwona; Domański, Leszek; Gołembiewska, Edyta (Frontiers in Medicine, 2024)
Objectives: The number of relevant markers of local intraperitoneal inflammation in patients treated with peritoneal dialysis (PD) is scarce. Therefore the aim of the study was to establish the compatibility of peritoneal effluent (PE) with proteomic studies and the potential utility of PE in immunoprofiling studies. Methods: This pilot study included six PD patients at the Peritoneal Dialysis Center, Department of Nephrology, Transplantology and Internal Medicine, Szczecin, Poland. The patients were clinically stable, with no signs of infections or malignancy at the time of study. The PE samples were collected during routine surveillance at Peritoneal Dialysis Center and the proteomic analysis was done using the Olink® Target 48 Cytokine panel. Results: PE samples were successfully analyzed with 28 out of 45 proteins which were found within the Limit of Quantitation (LOQ) and 32 out of 45 proteins above the Limit of Detection (LOD). No significant interference on the assay from the matrix was observed. Biomarkers associated with low grade inflammation achieved varied levels. The patterns of these were comparable in all of the patients. Conclusions: This study suggests that cytokine panel with relative quantification is a promising method for PE immunoprofiling.